一个生生不息的行业 ：新加坡华人殡葬业洪振茂寿板店案例研究 = A matter of life and death : Ang Chin Moh Casket, a chinese family funeral business in Singapore. - 林颖娴 Lin, Ying Xian (2013)
新加坡华人殡葬业曾在20世纪初欣欣向荣，1960年代因城市规划沉静下来，1990年后新一代逐渐接手父业，在过程中经历了家族企业的传承问题，以图面对时代步伐。本论文着重探讨华人殡葬业者作为家族企业如何继承和转型，通过与洪振 茂寿板店的访问，探讨华人家族企业如何与家族以外的人员合作，以及企业在历史中的演变。研究显示，洪振茂寿板店得以传承是因为给予有能力的人选经营的权力，但同时也开放给非家族成员的加入，以提高企业的专业性。研究也显示，本地殡葬业也面临着空间不足、 缺乏专业性教育、缺乏新血、人手老化、人手不足及设施不足等挑战。The funeral industry in Singapore flourished during the early 20th century and toned down in the 1960s when urban planning took place. New blood of the funeral industry took over the older generation after the 1990s, having to face the changes in the management of their family businesses, while at the same time, keeping up with times. This project explores the organizational hierarchy of the Chinese funeral business, looking at how it has been passed down over generations. Through a case study on Ang Chin Moh Casket, we examine how the non-family members can be involved in the family business, and as well as how business strategies have been adopted throughout the years. The findings have shown that while only the capable members inherit the family business, non-family members are welcomed to the family business as well in order to cultivate a higher professionalism in business management. The funeral industry in Singapore are facing several challenges, such as the lack of space, new blood, professional training, manpower, and good facilities.